2022
DOI: 10.3389/fspor.2022.830492
|View full text |Cite
|
Sign up to set email alerts
|

Use of Frame Running for Adolescent Athletes With Movement Challenges: Study of Feasibility to Support Health and Participation

Abstract: Children and adolescents with movement challenges have lower instances of physical activity and longer time spent in sedentary behaviors compared to children with typical development. The purpose of this study was to investigate the feasibility of a sport-based youth development running program modified for accessibility using a running frame and to evaluate initial evidence for its efficacy on endurance and functional strength. We completed four 8-week seasons (2–3 times per week) in a combination of 3 differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…They have shown that a child with diplegic CP at GMFCS Level II was able to improve his scores on the GMFM through ongoing engagement in the Dance Program. Sukal-Moulton and colleagues [98] similarly showed an improvement in self-efficacy and self-perception in an adolescent with diplegia following participation in a running program using a running frame for aerobic training, including engagement in a community race. At the conclusion of training, the participant stated, "we are a family of runners now" in reference to joining her parents and younger brother in running for fitness; this was followed by a study where group level differences were found [98].…”
Section: Maximizing Engagement and Addressing Barriersmentioning
confidence: 93%
See 2 more Smart Citations
“…They have shown that a child with diplegic CP at GMFCS Level II was able to improve his scores on the GMFM through ongoing engagement in the Dance Program. Sukal-Moulton and colleagues [98] similarly showed an improvement in self-efficacy and self-perception in an adolescent with diplegia following participation in a running program using a running frame for aerobic training, including engagement in a community race. At the conclusion of training, the participant stated, "we are a family of runners now" in reference to joining her parents and younger brother in running for fitness; this was followed by a study where group level differences were found [98].…”
Section: Maximizing Engagement and Addressing Barriersmentioning
confidence: 93%
“…Sukal-Moulton and colleagues [98] similarly showed an improvement in self-efficacy and self-perception in an adolescent with diplegia following participation in a running program using a running frame for aerobic training, including engagement in a community race. At the conclusion of training, the participant stated, "we are a family of runners now" in reference to joining her parents and younger brother in running for fitness; this was followed by a study where group level differences were found [98]. The inclusion of psychosocial features into any program designed to increase physical activity while augmenting bone and muscle health may significantly contribute to immediate and long-term sustainability and enrich quality of life [108].…”
Section: Maximizing Engagement and Addressing Barriersmentioning
confidence: 93%
See 1 more Smart Citation
“…Recent protocol studies (18)(19)(20) have provided a well-organized methodology for feasibility studies. Future studies can therefore shed light on the effects of FR practice on risk factors for cardiovascular diseases and functional mobility.…”
Section: Health and Quality Of Lifementioning
confidence: 99%